Behavioral profiles of three C57BL/6 substrains - Matsuo, Naoki; Takao, Keizo; Nakanishi, Kazuo; Yamasaki, Nobuyuki; Tanda, Koichi; Miyakawa, Tsuyoshi (Frontiers in Behavioral Neuroscience, 2010)
C57BL/6 inbred strains of mice are widely used in knockout and transgenic research. To evaluate the loss-of-function and gain-of-function effects of the gene of interest, animal behaviors are often examined. However, an issue of C57BL/6 substrains that is not always appreciated is that behaviors are known to be strongly influenced by genetic background. To investigate the behavioral characteristics of C57BL/6 substrains, we subjected C57BL/6J, C57BL/6N, and C57BL/6C mice to a behavior test battery. We performed both a regular scale analysis, in which experimental conditions were tightly controlled, and large-scale analysis from large number of behavioral data that we have collected so far through the comprehensive behavioral test battery applied to 700–2,200 mice in total. Significant differences among the substrains were found in the results of various behavioral tests, including the open field, rotarod, elevated plus maze, prepulse inhibition, Porsolt forced swim, and spatial working memory version of the eight-arm radial maze. Our results show a divergence of behavioral performance in C57BL/6 substrains, which suggest that small genetic differences may have a great influence on behavioral phenotypes. Thus, the genetic background of different substrains should be carefully chosen, equated, and considered in the interpretation of mutant behavioral phenotypes.